2002
DOI: 10.1097/00004479-200204000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Provider Characteristics Fostering Smoking Cessation Practice Guideline Adherence

Abstract: We examined the relationship between physician adherence with a smoking cessation guideline and organizational structures, policies, leadership support, and physician knowledge and attitudes. A random sample of 844 physicians practicing in 127 VHA hospitals was surveyed. Survey results were aggregated to the hospital level and linked with data on organizational characteristics from the 1998 annual survey of hospitals by the American Hospital Association. Significant predictors of adherence included organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 10 publications
3
30
1
Order By: Relevance
“…Study findings affirm evidence that tobacco dependence treatment is inconsistently offered in hospitals [14][15][16][17][18]25,29 and heath providers were uninformed about tobacco dependence treatment, 29 despite availability of nicotine-replacement therapy at study sites. This treatment gap is perplexing, especially as within Canada there exists an evidence-based hospital tobacco dependence treatment program.…”
Section: Patientssupporting
confidence: 58%
See 3 more Smart Citations
“…Study findings affirm evidence that tobacco dependence treatment is inconsistently offered in hospitals [14][15][16][17][18]25,29 and heath providers were uninformed about tobacco dependence treatment, 29 despite availability of nicotine-replacement therapy at study sites. This treatment gap is perplexing, especially as within Canada there exists an evidence-based hospital tobacco dependence treatment program.…”
Section: Patientssupporting
confidence: 58%
“…16,20,25 Like other researchers, we have found that when tobacco use is framed as a habit, health care providers are perplexed as to why people continue to smoke when faced with health concerns and restrictions, and consider such people to not be taking responsibility for their health. 25 This may be a root cause for the stigmatization of people who smoke, or at least for the lack of empathy toward them.…”
Section: Patientssupporting
confidence: 50%
See 2 more Smart Citations
“…Addressing barriers to the delivery of tobacco treatment including clinician knowledge, attitudes, skills, and time constraints is necessary to increase the uptake of tobacco treatment interventions in primary care settings 5,[14][15][16][17] . The 'Ottawa Model for Smoking Cessation' (OMSC), is a multicomponent intervention for addressing tobacco use with smokers in primary care settings that is based on the 5A's model 11,18,19 .…”
Section: Study Protocol Tobacco Prevention and Cessationmentioning
confidence: 99%